2001
DOI: 10.1177/194589240101500602
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Sinus Surgery and New Classification Proposal

Abstract: Complication overviews may lead to measures directed toward quality improvement and to better information for patients. When evaluating the rhinological literature from 1979 to 1999, a detailed comparison could not be made because of differences in reporting. With the advent of electronically stored medical data, events can be registered better than before. To be able to compile very diverse data from electronic dossiers into concise overviews for feedback, a simple general scale with broad categories is neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 76 publications
0
49
0
6
Order By: Relevance
“…After reporting on an initial incidence of complications, Stankiewicz 1355 demonstrated that after the experience of an additional 300 ethmoidectomies, the overall complication rate went from 29% down to 9.3%, suggesting that as experience with the procedure increased, the likelihood of complications decreased. Using the Rombout and de Vries 1357 criteria, Soyka and Holzmann 1356 retrospectively evaluated 421 endoscopic procedures of varied complexity as performed by surgeons of varied skill levels and found that there was an overall complication rate of 39.7%, which included both minor and major complications. However, there was no significant correlation between the experience of the surgeon and the incidence of complications.…”
Section: S169mentioning
confidence: 99%
“…After reporting on an initial incidence of complications, Stankiewicz 1355 demonstrated that after the experience of an additional 300 ethmoidectomies, the overall complication rate went from 29% down to 9.3%, suggesting that as experience with the procedure increased, the likelihood of complications decreased. Using the Rombout and de Vries 1357 criteria, Soyka and Holzmann 1356 retrospectively evaluated 421 endoscopic procedures of varied complexity as performed by surgeons of varied skill levels and found that there was an overall complication rate of 39.7%, which included both minor and major complications. However, there was no significant correlation between the experience of the surgeon and the incidence of complications.…”
Section: S169mentioning
confidence: 99%
“…Sphenopalatine artery, ethmoidal artery, and internal carotid artery are always at danger during Endoscopic sinus surgery leading to catastrophic complications. Injury to the Optic nerve in sphenoid sinus can cause permanent blindness [8]. All the above mentioned complications can be avoided by our method of using rubber catheter for AC Polyp resection.…”
Section: Discussionmentioning
confidence: 95%
“…We divided complications in (a) adverse events (spontaneous recovery), (b) minor complications (intervention needed, but without residual problems), (c) major complications (persistent problems) and (d) death [27].…”
Section: Adverse Events and Complicationsmentioning
confidence: 99%